Pheochromocytoma: about 2 cases - Muxi, Fernando; Varela, Ana María; Sandler, Alberto; Bielli, Hugo; Acosta Ferreira, Walter; Viola Peluffo, Julio; Delgado, Hugo (Cirugía del Uruguay, 1977)
Twv patients suffered from arterial hypertension caused by pheochromocytoma and were operated with immediate and removed success. Diagnosis was confirmed by pharmaco!ogical tests, hormone dosage and tumoral visualization by means of retropneumoperitoneum in one case, and arteriography in the other. Pre-operatory treatment with adrenergic alfa and beta blocking agents constitutes one of the fundamental pillars of operatory success.